2003
DOI: 10.1007/s00402-003-0591-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation at 6-month follow-up of plantar fasciitis after extracorporeal shock wave therapy

Abstract: After ESWT, the thickness of the plantar fascia in patients with plantar fasciitis decreased, pain and walking time improved (all significantly).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
49
3
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 35 publications
8
49
3
10
Order By: Relevance
“…Many treatment regimens exist but effectiveness is variable [8,52,55,63]. Multiple publications focused on the evaluation of a clinically relevant effect of shock wave application on plantar heel pain, either of high-energy extracorporeal shock wave treatment (ESWT), applied in a single session with local or regional anesthesia [3,6,9,28,35,36,38,59] or of lowenergy ESWT, applied repetitively without local anesthesia [1, 4,7,11,[20][21][22][23]27,[44][45][46]48,51].…”
Section: Introductionmentioning
confidence: 99%
“…Many treatment regimens exist but effectiveness is variable [8,52,55,63]. Multiple publications focused on the evaluation of a clinically relevant effect of shock wave application on plantar heel pain, either of high-energy extracorporeal shock wave treatment (ESWT), applied in a single session with local or regional anesthesia [3,6,9,28,35,36,38,59] or of lowenergy ESWT, applied repetitively without local anesthesia [1, 4,7,11,[20][21][22][23]27,[44][45][46]48,51].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated the effectiveness of palpation-guided or ultrasound (US)-guided steroid injection [2,8]. A number of studies have also reported highly positive results for ESWT with or without US guidance in treating plantar fasciitis [7,9]. High-resolution US (HRUS) is very reliable in the diagnosis of IPF, with a sensitivity of 80% and a specificity of 88.5% compared with the reference standard, magnetic resonance imaging (MRI) [5].…”
Section: Introductionmentioning
confidence: 96%
“…With the help of ultrasonograph they measured the plantar fasciitis' thickness of 2 cm distal to the tuberosity of the calcaneus before the therapy, 6, 12 and 24 weeks after the therapy, and compared them with the plantar fasciitis of a healthy foot. It turned out that 6 weeks after the shock wave therapy the plantar fasciitis thickness of the ill foot and its pain significantly decreased, that caused the locomotion improvement [6].In their next research Lizis and Hudakova compared the shock waves' and the ultrasound waves' influences on the improvement of the feet health status of the patients with calcaneal spur, whose heel spur pain lasted longer than 6 months. The patients treated with shock waves got the altogether dose of 7000 impulses of shock waves, energy flux density 0.4 ml/mm 2 during 5 treatments performed once a week for 5 weeks.…”
mentioning
confidence: 97%
“…With the help of ultrasonograph they measured the plantar fasciitis' thickness of 2 cm distal to the tuberosity of the calcaneus before the therapy, 6, 12 and 24 weeks after the therapy, and compared them with the plantar fasciitis of a healthy foot. It turned out that 6 weeks after the shock wave therapy the plantar fasciitis thickness of the ill foot and its pain significantly decreased, that caused the locomotion improvement [6].…”
mentioning
confidence: 99%